A diffuse reflectance portable near infrared spectroscopy system for the determination of biuret content in urea fertilizer. Issue 1 (February 2023) - Liu, Jing; Yu, Shaohui; Hu, Shupeng; Ling, Ziyang; Gao, Jiguang; Liu, Binmei; Yu, Lixiang; Yang, Yang; Yang, Ye; Wang, Qi; Ni, Xiaoyu; Zhao, Liping; et al.
Simple, rapid, and reliable determination of the biuret content in urea fertilizer is very important for the development of fertilizer industry. A near infrared diffuse reflectance measurement system with a portable spectrometer was developed, in which the reference and dark background spectrum could also be recorded automatically in addition to the absorbance data. The key performances of the proposed NIR system have been tested on urea fertilizer. Numerical experiments showed that the coefficient of determination (R 2 ) of the external validation set was 0.97, with a root mean square error (RMSE) of 0.04%. The ratios of the performance deviation (RPD) value in the calibration and validation sets were 12 and 3.5, respectively. It can be concluded that this NIR system for the determination of biuret content in urea fertilizer may potentially be used as an alternative method to traditional wet chemical methods due to its simplicity, sensitivity, and portability.